The usefulness of fleet rectal enemas on high-dose-rate intracavitary cervical cancer brachytherapy. A prospective trial - Andres, Ignacio; Gutierrez-Perez, Manuel; Rodriguez-Vela, Maria Pilar; Berenguer, Roberto; Sevillano, Marimar; Aguayo, Manuel; Arenas, Meritxell; Rovirosa, Angeles; Murria-Perez, Yashmina; Sabater, Sebastia (Journal of Contemporary Brachytherapy, 2017)
Purpose: To evaluate the effects of rectal enemas on rectal doses during radical high-dose-rate (HDR) intracavitary cervical brachytherapy (BT). Material and methods : Twenty patients suffering from cervical cancer and treated with external beam radiotherapy and HDR-BT were included in a prospective trial. The first brachytherapy fraction was considered the basal status, and patients were instructed to self-administer two rectal cleansing enemas before the second fraction. Dose-volume histogram (DVH) values were generated for the rectum and correlated with rectal volume variation. Brachytherapy was carried out with a Fletcher or Utrecht applicator. Results : No significant rectal volume differences were observed between fractions with or without rectal enemas (without, 52.64 ± 15.92 cc; with, 53.16 ± 19.28 cc). There was a significant correlation between both rectal volumes (r = 0.722, p = 0.001). No significant differences were observed in analyzed DVH parameters (median values: ΔD 0.1cc , 4.17 vs. 3.61 Gy; ΔD 1cc , 3.23 vs. 2.87 Gy; Δ D2cc , 2.9 vs. 2.54 Gy; ΔD 5cc , 2.35 vs. 2.05 Gy, for no enema and enema fraction, respectively). No significant rectal volume differences nor DVH parameter differences were observed according the applicator type. Conclusions : Our rectal enemas protocol prior to HDR-BT was ineffective in significantly modifying rectal DVH parameters. No differences were observed according to the type of applicator used.